A single session of laser ablation for toxic thyroid nodules: three-year follow-up results. (4th July 2018) - Gambelunghe, Giovanni; Stefanetti, Elisa; Colella, Renato; Monacelli, Massimo; Avenia, Nicola; De Feo, Pierpaolo
Abstract: Purpose: To confirm the effectiveness of laser ablation on toxic nodules in a large population with three years of follow-up. Material and methods: Between 2009 and 2014, we treated 82 patients with hyperthyroidism related to the presence of a toxic nodular goitre. Patients were pre-treated pharmacologically with methimazole prior to single session of laser ablation (LA) and then followed up every 3 months with FT4 and TSH blood tests as well as ultrasound examination of the nodules treated. Results: All patients responded to the treatment. The median nodule volume decreased from 12 ml (range 5–118 ml) to 5 ml (range 1.2–40 ml) after three years ( p  < 0.001). The percentage of patients who discontinued methimazole therapy was reduced by increasing the initial volume of the toxic nodule. In nodules with a volume less than 5 ml, all patients were able to suspend methimazole; this percentage was reduced to 90.2% in nodules with a volume between 5 and 15 ml, 61.1% in those with volume 15–25 ml and only 28.5% in nodules larger than 25 ml. We had no major complications but only moderate pain and fever in the evening, a few hours after ablation therapy in 10% of treated patients. Conclusions: Single session of LA of toxic thyroid nodules is effective and safe, especially in nodules with a volume under 15 ml.